Efektivitas Model Pembelajaran Project Based Learning dengan Media Stick and Plasticine terhadap Hasil Belajar Matematika Siswa Kelas IV - Ni'mah, Khoirun; Noviana Dini Rahmawati; Kartinah; Evy Ariestanti (Jurnal Lensa Pendas, 2024)
This study aims to determine the effectiveness of project-based learning using stick and plasticine media on Mathematics learning outcomes among fourth-grade students of SDN Sendangguwo 01 Semarang. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 28 students from class IVB SDN Sendangguwo 01 Semarang. Data were collected through tests and documentation. The results were analyzed using the Wilcoxon signed-rank test and N-gain calculation. The Wilcoxon test was chosen due to the non-normal distribution of the data. The findings indicated a significant Asymp.Sig. (2-tailed) value of 0.000<0.05, thus supporting the alternative hypothesis (Ha). The N-gain analysis categorized the effectiveness as moderate, with an N-gain score of 0.5830 and a percentage N-gain of 58.3007. Therefore, the project-based learning model using stick and plasticine media significantly proved to be moderately effective in enhancing Mathematics learning outcomes among fourth-grade students at SDN Sendangguwo 01 Semarang. This research is expected to contribute to educational practices.